Mustard and salinity tolerance: A resilient oilseed for the future - Watts, Archana; Sardar, Shaswati; Gandhi, Silky; Watts, Anshul; Yadava, Pranjal; Ray, Soham; Nagar, Shivani (Indian Farming, 2025)
Salinity is one of the major abiotic stresses limiting crop production and productivity, particularly in the arid and semi-arid regions of India. Indian mustard (Brassica juncea), a leading oilseed crop valued for its culinary and medicinal properties, is highly susceptible to salt stress, which causes significant yield losses. The adverse effects include reduced seed germination, stunted plant growth, decreased seed yield, and a decline in oil content. Exploring the genetic variation within mustard germplasm offers opportunities for developing salt-tolerant cultivars. A comprehensive understanding of morphological, physiological, and molecular mechanisms underlying salt tolerance is crucial for this purpose. Strategies such as exploiting existing germplasm, adopting improved breeding techniques, implementing effective agronomic practices, and applying advanced technologies like genome editing hold great potential for enhancing salt tolerance in mustard. Integration of conventional breeding with modern genomic tools and genome-editing approaches will facilitate the identification and functional validation of key candidate genes and regulatory networks, thereby accelerating the development of resilient mustard cultivars for saline environments.